Effect of Alcoholic Extract of Nigella Sativa on Cisplatin-induced Toxicity in Rat (Iranian Journal of Kidney Diseases, 2012)
Introduction. The aim of this study was to test whether Nigella sativa (NS) seeds can reduce cisplatin-induced toxicity. Materials and Methods.  Thirty rats were divided into 3 groups to receive distilled water (control group), cisplatin (3 mg/kg per body weight for 3 days), and cisplatin and alcoholic extract of NS (100 mg/kg per body weight). Biochemical and histopathologic parameters were compared between the three groups on days 14 and 42 of the study. Results. Blood urea nitrogen increased in the cisplatin and NS groups on days 14 and 42 compared to day 0 (P < .001). It was significantly in the cisplatin than in the control group on day 14 (P < .001). Serum creatinine had a similar profile in the cisplatin and NS groups as blood urea nitrogen. Serum triglyceride increased in the cisplatin and NS groups on day 14, but it decreased on day 42 (P < .05). Urine glucose concentration decreased in the cisplatin group on days 14 and 42 compared to day 0 (P < .001), and the same trend was seen in the NS group (P < .001). Histology of the kidneys exposed to cisplatin showed significant kidney injury, but the rats treated with NS showed a relatively well-preserved architecture. Conclusions. Cisplatin-induced nephrotoxicity was confirmed in our study. Nigella sativa seeds had nonsignificant effects on biochemical parameters, although the histopathologic properties of the kidneys relatively recovered after NS use.